2013
DOI: 10.1007/s12687-013-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance based on genetic medicine: a literature review

Abstract: For this literature review, medical literature data bases were searched for studies on patient compliance after genetic risk assessment. The review focused on conditions where secondary or tertiary preventive options exist, namely cancer syndromes (BRCA-related cancer, HNPCC/colon cancer), hemochromatosis, thrombophilia, smoking cessation, and obesity. As a counterpart, patient compliance was assessed regarding medication adherence and medical advice in some of the most epidemiologically important conditions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 122 publications
(149 reference statements)
0
23
0
1
Order By: Relevance
“…Tingkat kepatuhan tinggi justru dimiliki oleh kelompok responden yang tidak memiliki keluarga dengan riwayat hipertensi. Hasil ini serupa dengan penelitian yang dilakukan oleh Schneider 23 yang menyatakan bahwa faktor riwayat keluarga yang memiliki suatu penyakit tertentu tidak menjamin kepatuhan seseorang terhadap penyakit tersebut secara langsung, hal ini disebabkan karena dibutuhkan suatu proses pemahaman terlebih dahulu sebelum kepatuhan itu muncul.…”
Section: Pembahasanunclassified
“…Tingkat kepatuhan tinggi justru dimiliki oleh kelompok responden yang tidak memiliki keluarga dengan riwayat hipertensi. Hasil ini serupa dengan penelitian yang dilakukan oleh Schneider 23 yang menyatakan bahwa faktor riwayat keluarga yang memiliki suatu penyakit tertentu tidak menjamin kepatuhan seseorang terhadap penyakit tersebut secara langsung, hal ini disebabkan karena dibutuhkan suatu proses pemahaman terlebih dahulu sebelum kepatuhan itu muncul.…”
Section: Pembahasanunclassified
“…94 However, depressive symptoms in mutation carriers were associated with poor adherence to colonoscopy. 95 Positive family relationships also predicted increased adherence to recommended screening.…”
Section: Hnpccmentioning
confidence: 99%
“…A recent review found conflicting results on whether smoking cessation-a major behavioural risk factor for stroke-was increased after genetic profiling for the glutathione S-transferase M1 (GSTM1) gene status, which is associated with risk of lung cancer. 33 The . Detection of a significant association does not mean that the identified SNP is causal; it is usually merely a marker for a causal functional SNP that is located on a nearby region of the genome.…”
Section: Implications For the Clinicianmentioning
confidence: 99%